Digital Radiography with Computerized Conventional Monitors Compared to Medical Monitors in Vertical Root Fracture Diagnosis - Tofangchiha, Maryam; Adel, Mamak; Bakhshi, Mahin; Esfehani, Mahsa; Nazeman, Pantea; Ghorbani-Elizeyi, Mojgan; Javadi, Amir (Iranian Endodontic Journal, 2013)
Introduction: Vertical root fracture (VRF) is a complication which is chiefly diagnosed radiographically. Recently, film-based radiography has been substituted with digital radiography. At the moment, there is a wide range of monitors available in the market for viewing digital images. The present study aims to compare the diagnostic accuracy, sensitivity and specificity of medical and conventional monitors in detection of vertical root fractures. Material and Methods: In this in vitro study 228 extracted single-rooted human teeth were endodontically treated. Vertical root fractures were induced in 114 samples. The teeth were imaged by a digital charge-coupled device radiography using parallel technique. The images were evaluated by a radiologist and an endodontist on two medical and conventional liquid-crystal display (LCD) monitors twice. Z-test was used to analyze the sensitivity, accuracy and specificity of each monitor. Significance level was set at 0.05. Inter and intra observer agreements were calculated by Cohen’s kappa. Results: Accuracy, specificity and sensitivity for conventional monitor were calculated as 67.5%, 72%, 62.5% respectively; and data for medical grade monitor were 67.5%, 66.5% and 68% respectively. Statistical analysis showed no significant differences in detecting VRF between the two techniques. Inter-observer agreement for conventional and medical monitor was 0.47 and 0.55 respectively (moderate). Intra-observer agreement was 0.78 for medical monitor and 0.87 for conventional one (substantial). Conclusion The type of monitor does not influence diagnosis of vertical root fractures.